2001
DOI: 10.1073/pnas.171202698
|View full text |Cite
|
Sign up to set email alerts
|

Does oxidative damage to DNA increase with age?

Abstract: The levels of 8-oxo-2-deoxyguanosine (oxo8dG) in DNA isolated from tissues of rodents (male F344 rats, male B6D2F1 mice, male C57BL͞6 mice, and female C57BL͞6 mice) of various ages were measured using sodium iodide to prevent oxidative damage to DNA during DNA isolation. Oxo8dG was measured in nuclear DNA (nDNA) isolated from liver, heart, brain, kidney, skeletal muscle, and spleen and in mitochondrial DNA (mtDNA) isolated from liver. We observed a significant increase in oxo8dG levels in nDNA with age in all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
426
2
6

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 700 publications
(462 citation statements)
references
References 42 publications
(35 reference statements)
21
426
2
6
Order By: Relevance
“…With this method, we found no differences in young (3 month) liver, less damage in dwarfs at 12 months and in old dwarfs (24 month) higher 8-OH2dG:2dG ratios compared to controls. A recent report supported earlier studies demonstrating significant age-related increases in 8OHdG in both nuclear and mitochondrial DNA from various tissues of mice and rats (40). Early reports showed that normal oxidative damage to both nuclear and mitochondrial DNA was extensive (41).…”
Section: Discussionsupporting
confidence: 80%
“…With this method, we found no differences in young (3 month) liver, less damage in dwarfs at 12 months and in old dwarfs (24 month) higher 8-OH2dG:2dG ratios compared to controls. A recent report supported earlier studies demonstrating significant age-related increases in 8OHdG in both nuclear and mitochondrial DNA from various tissues of mice and rats (40). Early reports showed that normal oxidative damage to both nuclear and mitochondrial DNA was extensive (41).…”
Section: Discussionsupporting
confidence: 80%
“…One of the most advanced theories of aging is free radical theory proposed by in 1956 by D. Harman [58,59,253]. This theory postulated that various oxidative reactions occurring in the organism (mainly in mitochondria) generate free radicals as byproduct which cause multiple lesions in macromolecules (nucleic acids, proteins and lipids), leading to their damage and aging.…”
Section: Oxidative Stress In Aging and Carcinogenesismentioning
confidence: 99%
“…Likewise, human lifespan is of the same order of magnitude as observed A. islandica lifespan (122 and 36-226 years, respectively). In contrast, DNA oxidation increases much faster in short-lived rodents: 21-370 % over a rodent's 18-month lifespan in several tissues (Hamilton et al 2001). Because the biologies of humans, rodents, and clams differ, our results stress the advantage of intraspecific damage-marker comparison between populations with different maximum lifespans.…”
Section: Discussionmentioning
confidence: 72%